Pengembangan Ruang Terbuka Hijau berdasarkan Distribusi Suhu Permukaan di Kabupaten Bandung - Siti Badriyah Rushayati; Hadi S. Alikodra; Endes N. Dahlan; Herry Purnomo (Universitas Muhammadiyah Surakarta, 2011)
Bandung Regency is experiencing increased of air temperature, particularly in the urban area. High air temperature in urban areas is caused by increasing built-up areas and declining green open space. Green open space should be built to lower air temperature and to create a comfortable micro climate. Green open space should be developed at locations with high air temperature to reach its efficacy. This research used spatial analysis to generate air temperature distribution map. The map was used as the basis in developing green open space. The map showed that green open spaces should be developed at several sub-districts, namely Margahayu, Margaasih, Dayeuhkolot, Baleendah, Bojongsoang, Rancaekek, Cileunyi, Pameungpeuk, and Majalaya sub-districts.